Perancangan Sistem Informasi Monitoring Project Produksi Berbasis Web Pada PT. Cakra Abadi - Arisman laia; Kecitaan Harefa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Monitoring system is a system that functions to monitor, supervise and control an activity in a job. The monitoring system plays an important role for a company in processing data such as client data, employee data, project data, task data that includes deadlines and report data to optimize supervision of the company. Data processing system at PT. Cakra Abadi still uses conventional or Microsoft Excel so that the data has not been archived optimally. To handle this, a special application was made to monitor and manage production data in the company. The monitoring system can generate and manage data such as client data, employee data, project data, deadlines, task data and report data. This application is made using the waterfall method. In this monitoring system, it is very necessary to monitor the work of previous employees with the current one. The results of this monitoring system application design indicate that the role of computer applications in information systems is very important as a support in improving the quality of work in managing data. To improve work effectiveness and provide information quickly and accurately, this application was built using the PHP programming language and MySql as a database, with Unified Modeling Language (UML) tools.